The Interplay of Public Health Law and Industry Self-Regulation: The Case of Sugar-Sweetened Beverage Sales in Schools - Mello, Michelle M. (American Public Health Association, 2008)
It is increasingly recognized that sugar-sweetened beverage consumption contributes to childhood obesity. Most states have adopted laws that regulate the availability of sugar-sweetened beverages in school settings. However, such policies have encountered resistance from consumer and parent groups, as well as the beverage industry. The beverage industry’s recent adoption of voluntary guidelines, which call for the curtailment of sugar-sweetened beverage sales in schools, raises the question, Is further policy intervention in this area needed, and if so, what form should it take? We examine the interplay of public and private regulation of sugar-sweetened beverage sales in schools, by drawing on a 50-state legal and regulatory analysis and a review of industry self-regulation initiatives.